Total phenolic content, flavonoid content, and agromorphological diversity of butterfly pea accessions in Bengkulu, Indonesia. - Prameswari, W.; Yulian, Y.; Oktoviani, O.; Sari, D. K.; Situmeang, K. (International Journal of Agricultural Technology, 2025)
The results showed that the three accessions of Clitoria ternatea had phenotypic diversity of flowers and flower colors, namely dark blue-double petal (CTE_002), light blue-single petal (CTE_006), and light purple-single petal (CTE_013. In addition, the three accessions of Clitoria ternatea also had total monomeric anthocyanin content, total phenolic content, and total flavonoid content determined in the ethanol extract of the sample. Accession CTE_002 with dark blue-double petals had a total monomeric anthocyanin, phenolic, and flavonoid content of 56.76 ± 1.32 mg/l. 40.82±1.40mg GAE/g DW, and 4.76±0.72 mg QE/g DW. Variability in the anthocyanin content of the three accessions was only found in flowers with values ​​ranging from 12.38±0.33 - 56.76±1.32 mg/l. The phenolic content of the three accessions ranged from 33.38 ± 0.37 - 40.82 ± 1.40 mg GAE/g DW. This shows that the three clitoria ternatea accessions in Bengkulu Province have high phenolic content and extract yield. Therefore, this accession can be used commercially in the food and cosmetics industry and shows high potential for medicinal plant breeding programs.